2021
DOI: 10.1088/1755-1315/689/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the organo-mineral complex on the growth dynamics of the Scenedesmus quadricauda culture

Abstract: The paper presents data on the biotechnology of growing accumulative cultures of algae Scenedesmus quadricauda when adding organo-mineral complex drag to the culture growth medium. It is shown that the trace elements that make up the drug (trade name “Helavit”), at the studied concentrations, act in various ways stimulating and inhibiting the growth of algological culture. Having a different effect in the concentration range from 0.1 to 1 mg / L. The maximum positive effect is achieved with a drug concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…An important task of agriculture is to increase the production of high-quality livestock products. The solution to this problem is considered to be a complete feeding of animals, which is achieved mainly with the help of various mineral additives (Bublik et al, 2003;Golovacheva, Bychkova et al, 2020;Golovacheva, Kozlov et al, 2020;Gubajdullin et al, 2008;Simakov et al, 2020;Nikiforov-Nikishin et al, 2021). It was found that minerals have a positive effect on the metabolic processes and productivity of animals, while increasing the body's resistance to pathogens of infectious diseases (Golovacheva, 2004;Golovacheva, Nikiforov-Nikishin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An important task of agriculture is to increase the production of high-quality livestock products. The solution to this problem is considered to be a complete feeding of animals, which is achieved mainly with the help of various mineral additives (Bublik et al, 2003;Golovacheva, Bychkova et al, 2020;Golovacheva, Kozlov et al, 2020;Gubajdullin et al, 2008;Simakov et al, 2020;Nikiforov-Nikishin et al, 2021). It was found that minerals have a positive effect on the metabolic processes and productivity of animals, while increasing the body's resistance to pathogens of infectious diseases (Golovacheva, 2004;Golovacheva, Nikiforov-Nikishin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%